A New Surgical Technique for Internal Shoulder Contractures Secondary to Obstetric Brachial Plexus Injury: An Anterior Coracohumeral Ligament Release - Sarac, C.; Hogendoorn, S.; Nelissen, R.G.H.H. (Journal of Brachial Plexus and Peripheral Nerve Injury, 2019)
Background Obstetric brachial plexus injuries result from traction injury during delivery; 30% of these children sustain persisting functional limitations related to an external rotation deficit of the shoulder. The aim of this study was to compare the intraoperative gain in external rotation after a posterior subscapular release and an anterior coracohumeral ligament release.Methods This is a prospective study on 102 children with an internal rotation contracture of the shoulder who received either a posterior subscapular release (posterior skin incision along the medial border of the scapula of 3–5 cm) or an anterior (5-mm skin incision) coracohumeral ligament release between 1996 and 2010. After general anesthesia, internal and external rotations in both adduction and abduction were measured before and after the surgical release.Results After a posterior subscapular release, the intraoperative external rotation improved with a mean of 64 degrees (95% confidence interval [CI]: 54–74; p < 0.001) in adduction and with a mean of 41 degrees (95% CI: 32–49; p < 0.001) in abduction. After an anterior coracohumeral ligament release, external rotation increased with a mean of 61 degrees (95% CI: 56–66; p < 0.001) in adduction and a mean of 42 degrees in abduction (95%CI: 39–45, p < 0.001). Differences between these two groups were not statistically different.Conclusion The anterior release technique shows comparable results with the posterior subscapular release. And since it is performed through a smaller incision of 5 mm, this is our preferred method to increase passive external rotation.Level of evidence II.
Keywords: birth injuries; muscle skeletal surgery; brachial plexus injuried child; brachial plexus surgery